Nursing Care for a Patient with NSTEMI Admitted to the Coronary Care Unit for Percutaneous Coronary Intervention — A Case Study - M. S. SITI MARYATI; R. (II) P. DIOSO (ASEAN Journal on Science and Technology for Development, 2017)
This case studyaims to demonstrateclinical nursing skills to a patient with myocardial infarction admitted for percutaneous coronary intervention. Nursing care for this patient startedwith a physical assessment and laboratory invesigation analysis. This evaluation was necessary to develop a nursing care plan. The activities in the ward enumerated the medications provided, and the details of the vital signs monitored hourly. The patient was sent to cardiac catheter laboratory at 1030H. From the cardiac catheter laboratory post-percutaneouscoronary intervention to the mid-right coronary artery (1 Drug-Eluting Stent) he was transferred out to Telemetry unit on 11 August2016 at 1500H with Terumo band hemostatic device through radial approach